Determinants of Acute Respiratory Infections Incidence in Children Under Five in the Working Area of the Siak Hulu II Community Health Center in Kampar Regency - Alamsyahi, Agus; Kurniya, Tri; Ikhtiaruddin, Ikhtiaruddin; Rasyid, Zulmeliza (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The incidence of acute respiratory infections (ARIs) is high among under-five children, especially in developing countries. ARIs are a leading cause of morbidity and mortality in under-five children worldwide. ARIs in children take a heavy toll on life. ARI disease ranks first in the spread of illness in the Siak Hulu II Public Health. AIM: This study aims to determine the incidence of non-pneumonia ARI in children under five in the working area of the UPTD Siak Hulu II. METHODS: This research uses quantitative methods with a cross-sectional approach. The sample in this study was 74 children under five aged 12–59 months using the consecutive sampling technique. Data analysis used Chi-square, univariate and bivariate statistical tests. RESULTS: The results showed that there was a relationship between birth weight p = 0.017 and OR = 4.844, cigarette smoke exposure p = 0.012, indiscriminate snacking p = 0.013, maternal knowledge p = 0.016, and exclusive breastfeeding p = 0.038, with the incidence of non-pneumonia ARI in toddlers aged 12–59 months in the working area of the Siak Hulu II Health Center, Siak Hulu District, Kampar Regency. Respondents who have low birth weight have a 4.8 times greater risk of suffering from ARI. CONCLUSION: There is a relationship between birth weight, exposure to cigarette smoke, casual snacks, knowledge of mothers, and exclusive breastfeeding with the incidence of ARI in children under five in the work area of the UPTD Siak Hulu II Community Health Center, Siak Hulu District, Kampar Regency.